Association of Lipid Accumulation Product With Insulin Resistance and Metabolic Syndrome in Type 2 Diabetic Patients In Relation With Dietary Habit in Bangladeshi Population - Yeasmin, Roksana; Rahman, Aminur; Hoque Bhuiyan, Md Nizamul; Islam, Fahmida; Hasan, Rokibul; Aziz, Murshida (Bangladesh Journal of Medicine, 2022)
Background: Lipid accumulation product (LAP) is a novel biomarker of central lipid accumulation related to diabetes and cardiovascular disease risk. In this study, we assessed the association of LAP with glucose homeostasis, lipid profile parameters, and some clinical parameters about fast food-taking habits of diabetic patients. This study evaluated the relationship between lipid accumulating product (LAP) with insulin resistance and metabolic syndromeinfast food-taking patterns in the Bangladeshi type 2 diabetic population. Methods: Three hundred and seventy-five T2DM subjects as cases and three hundred and seventy-five healthyindividuals as control were assessed for anthropometric and biochemical measurements. LAP was calculated as [waist circumference (cm)–65]×[triglycerides (mmol/L)] in men, and [waist circumference (cm)–58]×[triglycerides (mmol/L)] in women. Associations of LAP with fasting glucose, insulin, insulin resistance index, and lipid profile levels, were assessed. Fast food-taking habits per week were also taken from the study subjects. Some clinical parameters (BMI, blood pressure, and waist-hip ratio) were also measured. Results: LAP was significantly correlated with glycemic markers like FBG, ABF,F. Insulin,HBA1C, HOMA-IR, HOMA B%, and Serc-HOMA in type-2 DM subjects. The p-value was less than 0.001. This study was alsosignificantly (p=<0.001) correlated with lipidemic markerslike TAG &LAP in type-2 DM subjects.LAP was significantly associated with BMI, waist-hip ratio (WHR), SBP, and DBP in T2DM subjects. Multiple comparisons of LAP with fast food-taking habits in the study population showed that mean LAP was significantly (p<0.02) higher in the positive fast food-taking habit-containing study group. Conclusion: LAP was significantly correlated with insulin resistance and metabolic syndrome in T2 diabetic subjects.The favorable, fast food-eating habit-containing study group had considerably greater LAP. Bangladesh J Medicine 2022; 33: 10-17